High Level of Serum Cholesteryl Ester Transfer Protein and Chemerin as a Risk Factor of Metabolic Syndrome in Adolescent Obese and the Description of Cholesteryl Ester Transfer Protein −629c/A Gene Promoter Polymorphism - Arimbawa, I. Made; Suastika, Ketut; Junitha, Ketut; Suryawan, I. Wayan Bikin; Husin, Michelle (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The prevalence of metabolic syndrome (MS) in children and adolescents has increased, along with increasing incidence of obesity. AIM: The aim of this study was to find out the polymorphism characteristic of cholesteryl ester transfer protein (CETP) -629C/A gene promoter and to prove that the CETP -629C/A polymorphism, serum CETP, and chemerin levels were risk factors of MS in obese adolescents. MATERIALS AND METHODS: A matched case–control study with obese adolescent aged 11–18 years was conducted from May to December 2017. Samples were consecutively recruited in seven junior and senior high schools in Denpasar. Case groups were obese adolescents with MS and control groups were obese adolescents without MS (non-MS obese). Both groups fulfilled eligibility criteria were matched by gender and puberty status. The study data were analyzed by Chi-square test and logistic regression with significant level p < 0.05. RESULTS: Analysis of CETP -629C/A polymorphism showed, AA and CA genotype were not a risk factors for MS when compared with CC genotype (OR = 0.81 [95% CI 0.23–2.88], p = 0.75 and OR = 0.95 [95% CI 0.38–2.37] p = 0.91, respectively). There was no significant difference between individual carriers A allele with individual carriers C allele to risk of MS (OR = 0.91 [95% CI 0.39–2.14], p = 0.83). The cutoff point of CETP levels was ≥2 μg/mL considered as CETP high levels, and <2 μg/mL considered normal; chemerin levels ≥170 ηg/mL considered as chemerin high levels, and <170 ηg/mL considered as normal. High levels of serum CETP were a risk factor in MS compared to normal levels (OR = 2.82 [95% CI 1.07–7.41], p = 0.036) and high levels of serum chemerin were a risk factor in MS compared to normal level (OR = 2.77 [95% CI 1.04–7.40], p = 0.042). CONCLUSION: This study concluded that high levels of serum CETP and chemerin were the risk factors for MS, while genotype AA CETP -629C/A gene polymorphism was not a risk factor for MS.